Salience and perceptions of epidemic-prone diseases in two communities: Findings from freelisting interviews in Khartoum State, Sudan. - Nada Abdelmagid; Omama Abdalla; Abdallah Yagoub; Abeer Taha; Altayeb Hyder; Awatif Yahia; Bashar Hassan; Marwa Ali; Mohammed Abdeen; Mustafa Adam; Nadeen Kamal; Nader Ezeideen; et al. (PLOS Global Public Health)
The frequency and severity of disease outbreaks disproportionately impacts settings affected by conflict or with weak health systems. Sudan, facing frequent and recurrent epidemics, struggles with limited resources. Understanding local perceptions of epidemic-prone diseases is vital for designing effective epidemic responses. This study describes the salience and perceptions of epidemic-prone diseases in two urban Sudanese communities. We conducted a cross-sectional qualitative study using freelisting in two communities in Khartoum State: Om Doum in Sharg al Neel locality and a neighbourhood in the Sixth Quarter of Ombadda locality. We purposively selected and interviewed consenting adults and recorded their responses to seven freelisting prompts. We analysed the data using Smith's salience index in Excel to evaluate the frequency and importance of terms, and used a relative salience index to compare terms between lists and sites. We interviewed 32 people in Om Doum and 30 in Ombadda. Epidemic-prone diseases, especially malaria, nose, sinus and throat infections (NSTIs), typhoid and COVID-19, were highly salient as common illnesses, recent outbreaks, and future infections and threats. Cancer and chronic diseases, while less salient, were important. Diseases highly salient as future threats, such as COVID-19 and cancer, were less salient, as likely future infections. Conversely, diseases highly salient as future infections, such as NSTIs and malaria, held lower salience for their future impact. This pattern was more pronounced in Ombadda. Infection prevention measures such as environmental hygiene were highly salient in both sites. Epidemic-prone diseases consistently emerged as significant concerns across sites, with local disease patterns shaping, but not fully explaining, perceived risks. While emphasising local disease burdens in risk communication is important, it may not be sufficient in all sites or for all diseases. Freelisting is useful for rapidly capturing the salience and perceptions of epidemic-prone diseases but requires complementary methods to explore nuanced patterns.